Prevalence of self-reported symptoms compatible with Carpal Tunnel Syndrome (CTS) among employees at a neonatal intensive care unit: a cross-sectional study / Prevalenza di sintomi compatibili con la Sindrome del Tunnel Carpale (STC) tra gli operatori di una unità di terapia intensiva neonatale: uno studio trasversale - Tsovili, E.; Rachiotis, G.; Touche, S. (La Medicina del Lavoro, 2012)
SummaryBackground: Carpal Tunnel Syndrome is a significant work-related disease. Objective: The aim of the study was to investigate the prevalence of symptoms possibly related to CTS in workers in a neonatal intensive care unit. Methods: The self-administered INRS questionnaire for musculoskeletal symptoms was distributed to all 41 employees of a neonatal intensive care unit and to an appropriate sample of 82 employees of a paediatric emergency department and an adult intensive care unit. Results: Employees of the neonatal intensive care unit recorded a significantly higher prevalence of symptoms potentially related to CTS in comparison with the reference group (58.5% vs 8.3%, respectively; p